Carpal Tunnel Syndrome - treatment - Jakub Litak; Cezary Grochowski; Joanna Litak; Paweł Szmygin; Bartłomiej Kulesza; Piotr Kamieniak (Kazimierz Wielki University, 2017)
Carpal Tunnel Syndrome is a common disease in General Practice. Clinical symptoms and Nerve Conduction Evaluation are crucial for proper diagnosis. Adequate treatment leads to pain relief. Thenar dystrophy indicates surgical treatment.